Tindak Tutur Asertif dalam Daftar Putar Pragmatik pada Kanal YouTube Kampus Virtual - Citra Resti Anggraini; Aisyah Salsha Febriana; Ela Indriyani; Sayka Absa Azzahra; Najma Sofi Yuliana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Hamlatus Sa’adah; Rofina Ayu Setia (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Speech is the main means of conveying the purpose and purpose of the conversation, which is manifested through speech according to the context. This study aims to (1) identify assertive speech actions in the "Pragmatic" playlist video on the Virtual Campus YouTube channel, and (2) explain the intent of the speech functions. The research method uses a qualitative descriptive approach with pragmatic theory, especially the act of assertive illocution. Data is collected through the technique of watching and recording by watching, transcribing, analyzing, classifying, and identifying speech. Analysis was carried out on six videos in the playlist, with the results finding 96 data on assertive speech actions. The findings were dominated by assertive speech actions stating (33 data), followed by justifying (19 data), and estimating (7 data). The results of the study showed that pragmatic learning videos used more assertive speech to express opinions, making it easier for students to understand the explanations given. The use of assertive speech also strengthens students' belief that explanations are based on the speaker's thoughts with relevant theoretical references. This research is expected to increase public understanding of the role of assertive speech in learning communication.